Modern Heritage in the UAE: the Central Market/Gold bazaar—Manifestations of Neo-Islamic Architecture in the Living City - Mohamed El Amrousi, and Feda Isam AbdulHafiz (International Journal of Advanced Science and Technology, 2020)
In the United Arab Emirates, especially Sharjah and downtown Abu Dhabi modernist architecture is now considered part of early attempt of sustainable design and heritage of the living city that reflects good design practices, especially after the establishment of the Urban Planning Council and Estidama Guidelines.  Madinat Zayed Gold Souk/bazaar still attracts many visitors because it represents a space of specialization, tt is also a representative of ‘modernism’ of  1970s Parallel examples such as the Central Market/Gold bazaar in Sharjah also manifest architectural attempts to create architecture within cultural and environmental contexts.  Traditional wind towers known as Barjeel, vaults, domes and arcades borrowed from the broader spectrum of Islamic arts, recreated in concrete act as architectural containers of heritage and spaces of socio-cultural interaction accessible to all social groups.  The aim of this research is to examine modern Arab ornament and its application on buildings in the downtowns of Abu Dhabi and Sharjah.  This research examines the environmental properties of the gold bazaars in Abu Dhabi and Sharjah using Formit architectural modelling software.  This study outlines the importance of forms of representation of form and identity in rapidly developing Arab cities and proposes a number of solutions/designs to improve the facades, and to enhance the comfort in the building then offers scenarios to make these buildings more sustainable